PROBLEM OF TABLE BEET ROOTS QUALITY AND WAYS OF SOLVING - V. I. Burenin; T. M. Piskunova; D. V. Sokolova (Овощи России)
The quality of table beet roots is determined by the complex traits and properties. Modern varieties of table beet are mostly heterozygous populations showing the strong variability under the influence of environmental conditions. Ecological and geographicalstudy of 165 accessions of table beet was carried out and the interrelationship between traits of quality and other important biologically and economically valuable traits such ascold resistance, early maturity, monogermicity, marketability was studied. The basic traits that characterize the quality of roots of beet, including their color and shape, and also chemical composition, marketability and storability at the long-term storage were described. The data on the inheritance of form and color of beet roots and their chemical composition were given. It was found that the reaction of different varieties and hybrids of beet to change of growing conditions was unequal that showed their genotypic differences. Early maturing varieties of table beet, characterized by the increased cold resistance, as a rule, had intensively colored flesh of roots and goodtaste. Relatively stable varietal trait in beet roots is a color. There was no stable relation between the chemical composition, the intensity of the color of flesh and taste. The result of the study of collection accessions showed negative relationship between the sugar content and betanin. It was established that was no significant differences in biochemical composition between monogerm and multigerm varieties of table beet. As  result of research, the valuable accessions of table beet of home and foreign breeding were revealed and recommended for use into modern breeding programs.